Nda-nwendaaganag (All My Relations): A relational approach to citation practices - Shawanda, Amy (Turtle Island Journal of Indigenous Health, 2023)
There is a scholarly gap regarding how to cite Nda-nwendaaganag (All My Relations) in academic writing. Nda-nwendaaganag encompasses both the animate and inanimate beings referred to as ‘All My Relations’. I have devised several ways for Indigenous scholars to refer to "All My Relations," because they are our collaborators, co-creators, and idea generators. The purpose is we acknowledge, honor, respect, celebrate, and to express our gratitude to Nda-nwendaaganag as contributors to our written work. In order to create the various methods for Nda-nwendaaganag, I gained motivation from the Baawaajige (Dream) Methods for citation inspiration (Shawanda, 2020). It was considering the critical moments in our time to record the source of knowledge, sacred space, and within seasons to capture when "All My Relations" shared and guided our knowledge. I categorize citation sources from an Anishinaabk worldview on the animate or inanimate. They are distinct in terms of how the information should be recorded for citation purposes. This includes things like the time of day/season, specific locations, and the geography of the generated theme, message, or idea. This will provide Indigenous students, scholars, and researchers to further decolonize settler knowledge systems. I hope that this resource will be useful to students, scholars, and researchers. I understand that it will not be accepted as valid citation practice within western sources, but it is a first step toward honouring and acknowledging Nda-nwendaaganag.